Inhibitory Effects of Natural Products on Germination, Outgrowth, and Vegetative Growth of Clostridium perfringens Spores in Laboratory Medium and Chicken Meat - Safa Q. Alfattani; Saeed S. Banawas; Mahfuzur R. Sarker (Microorganisms)
Clostridium perfringens type F is a spore-forming bacterium that causes human illnesses, including food poisoning (FP) and non-foodborne gastrointestinal diseases. In this study, we evaluated the antimicrobial activities of 15 natural products against C. perfringens spore growth. Among them, garlic, onion juice, and undiluted essential oil constituents (EOCs) of clove, rosemary, and peppermint showed the strongest activity. Therefore, we examined the inhibitory effects of these products on each stage of the life cycle of C. perfringens FP strains, including spore germination, spore outgrowth, and vegetative growth, in laboratory media and chicken meat. Both clove and peppermint oils (at 0.5%; v/v) inactivated C. perfringens spore germination in nutrient-rich trypticase–glucose–yeast extract (TGY) medium. Furthermore, EOCs at (0.1–0.5%) arrested the spore outgrowth of C. perfringens in TGY medium. Interestingly, EOCs at 0.5% completely inhibited the vegetative growth of FP isolates during a 6 h incubation in TGY medium. However, even at 4-fold higher concentrations (2%), EOCs were unable to inactivate C. perfringens spore growth in contaminated chicken meat stored under abusive conditions. Although some of the natural products inhibited C. perfringens spore germination, outgrowth, and vegetative growth in TGY medium, no such inhibitory activity was observed when these products were applied to C. perfringens spore-inoculated chicken meat.